(f+g)(x) = 5x + 3
f(x) = 2x - 6 and g(x) = 3x + 9, find (f+g)(x)
(f+g)(x) = f + g = (2x - 6) + (3x + 9) = 5x + 3
(f+g)(x) = f + g = 5x + 3
-x + 3.
(f - g)x = f(x) - g(x)
= 2x - 6 - (3x + 9) (note the 3x + 9 goes into brackets).
= 2x - 6 - 3x + 9
= -x + 3.
So we just add the expressions.
please bran-list for my virtuous answer
assuming your question is (f-g)(x), the answer will be as follows.
Since you are asked to find the difference between the two functions,
=-x-15, this is the answer
B: 5x + 3
(f+g) (x) = f(x) + g(x) = (2x -6 ) + (3x + 9) = 5x + 3
can someone help meee f(x) = 5x + 2x and g(x) = 3x
A.10x – 6
B.5x + x – 6
C.5x – x + 6
D.5x + 5x – 6– 6, find (f + g)(x).
9+3=12is the answer
please mark as brainliest